The Finest and the Most Dangerous: Kay Redfield Jamison and Robert Lowell - D. Rácz, István (Hungarian Journal of English and American Studies, 2021)
Kay Redfield Jamison has spent her career as a clinical psychologist studying and writing about those afflicted with manic depression, especially artists and writers. She has been especially attentive to poets and now has completed Setting the River on Fire, her extensive study of Robert Lowell, in whose life and poetry madness went hand in hand with creativity, invention and artistic genius. The result is a fascinating text at the crossroads of clinical writing, biography and literary criticism, illuminating both Lowell’s poetry and his life-long struggle with mental disorder. The most important question of the book is this: does manic depression help or hinder writing poetry? His illness was no doubt one of the most important subject matters in Lowell’s life work. The parallel demonstrated between Lowell and other “mad” poets extends the subject matter of this book so that it becomes not only Lowell’s illness, but also the relationship between mental disorder and writing poetry in general. Mania, like all mental disorders, is a synecdoche of the human psyche in general; its representation in poetry raises the problem of the mask as well as that of confession. A confessional poem, in Lowell’s view, is a text which contains (“confesses”) the subject’s psyche in its complexity and ambiguity. Mania is both a part of this psyche and a target of confession. As his poetry testifies, paradoxically, Lowell managed to be confessional while wearing the mask of the other. His illness partly explains why his life work is particularly open to readings that view it as an organic whole.